Carbon Dots Synthesized from Tofu Pulp for Liquid Tofu Waste Photo-degradation - Yosi Nurohman; Elisabeth Pratidhina; Emi Kurnia Sari; Wipsar Sunu Brams Dwandaru (Indonesian Review of Physics (IRiP), 2021)
This study was aimed to prepare and characterize carbon dots (CDs) from tofu pulp for liquid tofu wastes photo-degradation. The tofu pulp was dried, heated in an oven for an hour at 250 oC, mashed into powder, weighted as much as (g) 1; 2; 3; 4; and 5, dissolved into 100 ml distilled water, filtered, and characterized using UV-Vis, PL, and FTIR. The photo-degradation experiment was conducted for pure waste, waste + CDs, and waste + CDs + UV light, then the BODs were measured. The CDs reduced the wastes to 14.29% and 53.90% without and with UV light, respectively. The pure wastes, wastes + CDs, and wastes + CDs + UV light produced BOD values of (mg/l) 385; 200; and 135, respectively. The decrease in BOD showed that CDs with and without UV light successfully restore dissolved oxygen in the wastes.